Pemikiran Politik Ustadz Abdullah Sungkar - Muh. Nursalim (Millah: Journal of Religious Studies, 2003)
This paper is the result of research on the political thought of Abdullah Sungkar : The data found through, the observation on his recording of his religious proselytizing in many places, whether before his going to Malaysia or when he was been there. Other side, it found by the interview with some of his colleagues. The last one is to find the data about his life. The result of this research expresses that the person tends to have the literalism view in understanding the sacred text (al-Qur'ah). This kind of view has influenced on his political thought, for instance he refuses nationalism and democracy and puts on the obligation of standing of Islam Syari'ah.